Analysis of The Effect of Patient Eating Satisfaction On Food Waste: A Medical Informatics Perspective at Caruban Regional Hospital, Madiun Regency - Murtadlo, Ali; Ulfa, Maria (Journal of Health Education, 2024)
Background: Patient meal satisfaction is an important aspect of health services that can influence the patient's health and well-being. In the hospital context, this satisfaction is not only related to the quality of the food served but also to the management of food waste. High levels of food waste can have a negative impact on the environment and hospital operational costs. This research aims to explore the influence of patient eating satisfaction on the amount of food waste from the perspective of medical informatics produced at Caruban Hospital, Madiun Regency. Methods: This research method uses a cross-sectional study design with a population of patients treated at Caruban District Hospital. The data collection technique was carried out through a questionnaire adopted from ACHFPSQ and Schiavone to measure eating satisfaction. Data analysis was carried out using descriptive and inferential statistical methods. Results: These findings indicate that there is a significant relationship between the level of patient eating satisfaction and the amount of food waste produced. Patients who are satisfied with the food served tend to produce less food waste compared to those who are dissatisfied. Conclusions: The research conclusion is that there is a significant relationship between patient eating satisfaction and the amount of food waste at Caruban Regional Hospital. The overall level of patient satisfaction with the quality of food and hospital services is quite good, with a score of 3.94 ± 0.77. However, there are still complaints about the taste of 35% and the portion of the food served. Patients consume around 70.25% of the food provided, while the remaining 27.25% becomes waste. Socio-demographic factors such as age and cultural preferences also influence satisfaction, and the habit of bringing food from outside the hospital also contributes to increased waste.